Sex composition of living children in a matrilineal inheritance system and its association with pregnancy intendedness and postpartum family planning intentions in rural Ghana - Sebastian Eliason; Frank Baiden; Derek Anamaale Tuoyire; Kofi Awusabo-Asare (BMC, 2018)
Abstract Background Sex composition of living children within the context of "sex preference" and its association with various reproductive health outcomes has been extensively studied in South and South East Asia. Although sex preference has been observed in sub-Saharan Africa, there is paucity of research on sex composition of living children and its association with reproductive health behaviours and outcomes, particularly in a matrilineal inheritance system. The purpose of the study was to explore the existence of sex preference in a matrilineal inheritance system. Specifically, the study sought to better understand the issues by examining the sex composition of living children and how it is associated with reproductive outcomes such as pregnancy intendedness and intention to use postpartum family planning among women in a matrilineal area of Ghana. Methods This was a cross sectional study conducted at four selected health facilities in the Mfantseman municipality of the Central Region of Ghana. Out of the 1914 pregnant women attending antenatal clinic selected using total enumeration, from 2nd January to 30th April 2012, 1091 with living children and complete socio-demographic data were recruited for this study. Descriptive, chi square and multivariate logistic regression analyses were conducted. Results The mean age of the 1091 respondents in this study was 28.2 ± 6.0 years with mean gestational age of 26.7 ± 6.6 weeks. Whilst 78% of the women had at least a son, 71% had at least a daughter, with those having only sons exceeding those with only daughters by 6.3%. Also, majority of the women with more sons than daughters did not intend their current pregnancies. These observations, coupled with a sex ratio of 109 males to 100 females, inferred the existence of son preference. The levels of unintended pregnancy and intention to use postpartum family planning were high (70% and 78% respectively). There was an association between sex composition of living children and unintended pregnancy but no association between sex composition of living children and intention to use postpartum family planning. Women with only sons were 50% less likely to have unintended pregnancies compared to those with equal number of sons and daughters [AOR 0.5, 95% CI (0.3-0.8)]. Similarly, women over 30 years were 80% less likely to have unintended pregnancies compared to those 15-19 years [AOR 0.2, 95% CI (0.1-0.6)]. The women with parity of 5 or more and resident in Anomabo were more likely to have unintended pregnancy compared to those with parity of up to two [AOR 3.8, 95% CI (1.7-8.59)] and those resident in Saltpond [AOR 1.8, 95%CI (1.1-2.8), respectively. In addition, the women resident in Anomabo were more likely to have intention to use postpartum family planning compared to those in Saltpond [AOR 1.8, 95% CI (1.0-3.3)]. Conclusion There was persistence of more sons than daughters born in a predominantly matrilineal inheritance system and sex composition of living children had significant association with pregnancy intendedness but not with intention to use postpartum family planning.